SILICA NANOPARTICLES AS NANOCIDES AGAINST CORCYRA CEPHALONICA (S.), THE STORED GRAIN PEST - VANI C; BRINDHAA U (International Journal of Pharma and Bio Sciences, 2013)
Diatomaceous earth and synthetic silica have been used as insecticides in the form of inert dusts. Diatomaceous earth becomes more effective against insects if it possesses high amorphous silica content with uniform size distribution. Nanoparticles are more reactive than their bulk counterpart because of their increased surface to volume ratio. The objective of our study is to evaluate the effect of silica nanoparticles against the stored grain pest Corcyra cephalonica. Silica nanoparticles were synthesized by modified Stober’s sol-gel method. They were characterized by Scanning Electron Microscope, X-ray Diffraction and Energy Dispersive X-ray Spectroscopy. Characterization studies showed silica nanoparticles of size range 70-80nm were synthesized which are spherical in shape and amorphous in nature. The entomotoxic effect of silica nanoparticles were evaluated against the stored grain pest Corcyra cephalonica. Amorphous silica nanoparticles were found to be highly effective against this insect pest causing 100% mortality, indicating the effectiveness of silica nanoparticles to control insect pests.